New Fujita type results for quasilinear parabolic differential inequalities with gradient dissipation terms - Wang, Xiaomin; Fang, Zhong Bo (AIMS mathematics, 2021)
This paper deals with the new Fujita type results for Cauchy problem of a quasilinear parabolic differential inequality with both a source term and a gradient dissipation term. Specially, nonnegative weights may be singular or degenerate. Under the assumption of slow decay on initial data, we prove the existence of second critical exponents $ μ^{*} $, such that the nonexistence of solutions for the inequality occurs when $ μ < μ^{*} $.